Genome-wide significant association between a ‘negative mood delusions' dimension in bipolar disorder and genetic variation on chromosome 3q26.1 - Meier, Sandra Melanie; Strohmaier, Jana; Treutlein, Jens; Breuer, René; Schmäl, Christine; Rietschel, Marcella (Translational Psychiatry, 2012)
Research suggests that clinical symptom dimensions may be more useful in delineating the genetics of bipolar disorder (BD) than standard diagnostic models. To date, no study has applied this concept to data from genome-wide association studies (GWAS). We performed a GWAS of factor dimensions in 927 clinically well-characterized BD patients of German ancestry. Rs9875793, which is located in an intergenic region of 3q26.1 and in the vicinity of the solute carrier family 2 (facilitated glucose transporter), member 2 gene (SLC2A2), was significantly associated with the factor analysis-derived dimension ‘negative mood delusions' (n=927; P=4.65 × 10−8, odds ratio (OR)=2.66). This dimension was comprised of the symptoms delusions of poverty, delusions of guilt and nihilistic delusions. In case-control analyses, significant association with the G allele of rs9875793 was only observed in the subgroup of BD patients who displayed symptoms of ‘negative mood delusions' (allelic χ2 model: PG=0.0001, OR=1.92; item present, n=89). Further support for the hypothesis that rs9875793 is associated with BD in patients displaying ‘negative mood delusions' symptom, such as delusions of guilt, was obtained from an European American sample (GAIN/TGEN), which included 1247 BD patients and 1434 controls (PEA=0.028, OR=1.27).